On the relational structure of two tests measuring general pedagogical knowledge. - Seifert, Andreas; König, Johannes (EARLI SIG 11 Conference „Teaching and Teacher education in an Era of Accountabi-lity – What do we know and what do we need to know?”)

LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudie-renden: Zusammenhangsstruktur der Konstrukte der beiden Tests des pädagogi-schen Wissens. - Seifert, Andreas; König, Johannes (DGfE-Kongress „Erziehungs-wissenschaftliche Grenzgänge”)

Children's lexical skills and task demands affect gestural behavior in mothers of late-talking children and children with typical language development [Reprint] - Grimminger, Angela; Rohlfing, Katharina; Stenneken, Prisca (Gesture and Multimodal Development)

Educating each other's attention: Mothers' and infants' eye-contact within natural interactions at 3 and 6 months of age. - Szufnarowska, Joanna; Nomikou, Iris; Rohlfing, Katharina

Adapting the input collaboratively: the development of multimodal practices in early mother-infant interactions. - Nomikou, Iris; Rohlfing, Katharina

Adaptive maternal synchrony: multimodal practices are tailored to infants' attention - Nomikou, Iris; Lohan, Katrin Solveig; Rohlfing, Katharina

Infants' gaze modulates maternal multimodal input: A study with 3-month-olds - Nomikou, Iris; Lohan, Katrin Solveig; Rohlfing, Katharina

On the impact of institutional factors on general pedagogical knowledge. - Watson, Christina; Seifert, Andreas; König, Johannes (EARLI SIG 11 Conference „Teaching and Teacher education in an Era of Accounta-bility – What do we know and what do we need to know?)

Moderation des Symposiums "Entwicklung und Förderung von Kindern mit Zuwanderungsgeschichte im Vor- und Grundschulalter". Symposium auf dem 23. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hellmich, Frank; Koch, Katja; Hardy, Ilonka

Wirksamkeit eines wortschatzbasierten Lesestrategietrainings auf Lesekompetenzen von Grundschulkindern mit Deutsch als Zweitsprache. Vortrag auf der 21. Jahrestagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“ der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Förster, Sabrina; Hoya, Fabian Karl; Hellmich, Frank

Entwicklung diagnostischer Fähigkeiten bei Lehramtsstudierenden – Ergebnisse aus einer Trendstudie. Posterpräsentation auf der 21. Jahrestagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“ der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Hoya, Fabian Karl; Förster, Sabrina; Hellmich, Frank

Leseförderung durch ein wortschatzbasiertes Lesestrategietraining – Vorstellung eines evaluierten Konzepts für Kinder mit Deutsch als Zweitsprache. Vortrag auf der Tagung der Deutschen Gesellschaft für Lesen und Schreiben (DGLS) - Hellmich, Frank; Förster, Sabrina

Rückmeldungen im Unterricht und Kompetenzerwerb in der Grundschule - Hellmich, Frank

Rückmeldungen und Lernprozesse im Grundschulunterricht - Hellmich, Frank

Nonlocal Imaging by Conditional Averaging of Random Reference Measurements - Luo, Kai Hong; Huang, Bo-Qiang; Zheng, Wei-Mou; Wu, Ling-An (Chinese Physics Letters)

Tagungsbericht: 125. Jahresversammlung des Vereins für niederdeutsche Sprachforschung in Göttingen. - Wallmeier, Nadine (Korrespondenzblatt des Vereins für niederdeutsche Sprachforschung)

„Praktische Aktivitäten“ im physikbezogenen Sachunterricht der Grundschule und im physikalischen Anfangsunterricht der Sekundarstufe – ein Vergleich. - Tenberge, Claudia; Lange, Kim; Möller, Kornalia (Bedingungen des Lehrens und Lernens in der Grundschule – Bilanz und Perspektiven.)

Sozialräumlich orientierte Soziale Arbeit – Eine Spurensuche nach der Kategorie Gender - Landhäußer, Sandra (Soziale Arbeit und Geschlecht. Herausforderungen jenseits von Universalisierung und Essentialisierung.)
Debatten um Geschlecht und Diversity in der Sozialen Arbeit bewegen sich im Spannungsfeld zwischen theoretisch anspruchsvollen, z.T. aber unverbundenen Debatten und professionsbestimmenden fachlichen Ansätzen ohne Bezug zu Differenz. In der Praxis sozialpädagogischer Einrichtungen finden sich sowohl differenzsensible als auch essentialisierende und verallgemeinernde wie differenzblinde Konzepte. Der Sammelband bietet zunächst eine Übersicht über die theoretischen Diskurse zu Geschlecht, Diversität und Intersektionalität und einen Versuch, diese zueinander in Bezug zu setzen. Im zweiten Teil stellt er sich der Herausforderung, zentrale Ansätze der Sozialen Arbeit auf die Konsequenzen ihrer Ausblendung von Geschlecht u.a. sozialen Differenzen hin zu analysieren. Auf dieser Grundlage werden Ansätze für ihre differenzsensible Weiterentwicklung entworfen. Der dritte Teil widmet sich der Analyse des komplexen Verhältnisses zwischen Fokussierung bzw. Ausblendung von Differenzen und ihren jeweiligen Folgen in praktischer Sozialer Arbeit.

Development and integration of xerogel polymeric absorbance micro-filters into lab-onchip systems - Carregal-Romero, Ester; Fernandez-Sanchez, Cesar; Eguizabal, Alma; Demming, Stefanie; Büttgenbach, Stephanus; Llobera, Andreu (Opt. Express)
This work reports on the implementation of different absorption micro-filters based on a dye-doped hybrid organic-inorganic xerogel polymeric material synthesized by the sol-gel process. Microstructures containing eight different filter widths were fabricated in polydimethylsiloxane (PDMS), bonded to glass substrates and filled with the corresponding dye doped polymeric material by a soft lithography approach. The filtering capacity as a function of dye concentration and filter width was studied and revealed a linear dependence with both parameters, as expected according to the Beer-Lambert law. Zero passband transmittance values and relatively sharp stopband regions were achieved with all the filters, also showing rejection levels between ?6 dB and ?55 dB. Finally, such filters were monolithically integrated into a disposable fluorescence-based photonic lab-on-a-chip (PhLoC) approach. Calibration curves carried out with a model fluorophore target analyte showed an over two-fold increase in sensitivity and a thirty-fold decrease of the limit of detection (LOD) compared with the values recorded using the same PhLoC system but without the polymeric filter structure. The results presented herein clearly indicate the feasibility of these xerogel-based absorbance filtering structures for being applied as low-cost optical components that can be easily incorporated into disposable fluorescence-based photonic lab on a chip systems

Pre- and Post-FFT Interference Leakage Minimization for MIMO OFDM Networks - Lameiro, Christian; Vía, Javier; Santamaría, Ignacio; Heath Jr., Robert W. (Proc. Int. Symp. Wireless Comm. Syst.)
Interference alignment (IA) has been shown to achieve the maximum degrees of freedom in the multiple-input multiple-output (MIMO) K-user interference channel (IFC). In the presence of frequency-selective channels, orthogonal frequency-division multiplexing (OFDM) is typically used to deal with the multipath nature of the channel. While IA techniques can be applied in a per-subcarrier basis (post-FFT), the existence of symbol timing offsets (STOs) between the desired and the interfering OFDM symbols decreases the system performance dramatically. To solve this problem, we design pre-FFT precoders and decoders for single-beam MIMO IFCs for OFDM transmissions. Since the IA decoders operate before the FFT, they mitigate the interference before synchronization takes place. We show that our proposed scheme improves the system performance when STOs occur, in comparison with traditional post-FFT IA techniques. We provide simulation results to compare post- and pre-FFT beamforming techniques and to illustrate the performance of the proposed method.